The impact of strategic human resource management to optimize organizational performance: application of competencies analysis - Kabir, SMH; Haque, A. K. M. Ahasanul; Abdullah, Kalthom; Rahman, Mohammad Moshiur (2019)
Human resource management as a strategic function looks for different management skills in the job seekers during recruitment process. Management skills in the form of competencies are crucial to optimize organizational performance. Therefore, analysis of competencies is essential for job seekers to understand strategic directions of an organization. The objective of this study is to identify the competencies which are required in an interviewee by the human resource management to increase performance of an organization. This research will be accomplished by analyzing the application of competencies in business graduates who are seeking jobs in Malaysia. A qualitative research approach will be taken by having in-depth interviews of six business graduates from Kuala Lumpur and data will be analyzed systematically using Nvivo computer program. The study can be beneficial to the job seekers for preparing themselves more effectively according to the desired competencies to sustain in the ever-challenging job market in 21st century. The investigation can be carried out with more specific job industry with larger sample size for better understanding as a scope in future.